2023
DOI: 10.3390/su15054019
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Emergency Shelter Selection in Earthquakes Using a Risk-Driven Large Group Decision-Making Support System

Abstract: This study presents a novel risk-based decision support system for helping disaster risk management planners select the best locations for emergency shelters after an earthquake. The system starts by identifying 18 criteria, based on stakeholder analysis, that are important for selecting shelter sites. These criteria are then standardized to reflect their importance in the site selection process. Next, a Large Group Decision-Making (LGDM) model is used to determine the weight of each criterion based on collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These lead to the design perspectives of emergency shelters and evacuation areas for travelers and the surrounding population inside and around the railway station. Bakhshi Lomer et al [88] revealed that the criteria for selecting the optimal emergency shelters were proximity to the fault line, building topology and design concept, population density, availability of open and green areas, and the condition of the buildings. A refugee shelter can be designed in the area of the railway station building that encompasses both architectural and non-architectural elements, meeting international eligibility standards in terms of features, basic necessities, and evacuation actions [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…These lead to the design perspectives of emergency shelters and evacuation areas for travelers and the surrounding population inside and around the railway station. Bakhshi Lomer et al [88] revealed that the criteria for selecting the optimal emergency shelters were proximity to the fault line, building topology and design concept, population density, availability of open and green areas, and the condition of the buildings. A refugee shelter can be designed in the area of the railway station building that encompasses both architectural and non-architectural elements, meeting international eligibility standards in terms of features, basic necessities, and evacuation actions [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…In the OWA method, different operators and sets of ordered weights can be used to apply to a wide range of multi-criteria evaluation strategies [57]. A major objective of the OWA method is to provide decision makers with a quantitative assessment of a range of very optimistic to very pessimistic scenarios.…”
Section: Owamentioning
confidence: 99%
“…As the proximity to fault and landslide points increases, the location suitability increases since such events can cause serious damage [47]. Therefore, locations with a proximity of less than 1000 m were considered restricted areas.…”
Section: Proximity To Fault and Landslide Pointsmentioning
confidence: 99%